Adolescent Waterpipe Use is Associated with Greater Body Weight: The Irbid-TRY. (7th June 2018) - Alomari, Mahmoud A.; Al-Sheyab, Nihaya A.; Ward, Kenneth D.
ABSTRACT: Background : Adult waterpipe smokers are at increased risk of obesity. However, it is unclear if adolescents, who are at the epicenter of the global waterpipe epidemic, are at similar risk. Objective : Therefore, the current study examined the waterpipe smoking relationship with obesity among adolescents. Methods : A sample of 2, 313 boys and girls in grades 7–10 were surveyed about waterpipe and cigarette use in Jordan. Weight, body mass index (BMI), waist circumference, waist-to-hip ratio, and waist-to-height ratio were measured. Obesity indices were assessed as a function of smoking status (never used tobacco, current waterpipe only, current cigarettes only, and current dual smoking) as well as frequency of use of each tobacco product. Results : About 51.5% of adolescents smoked waterpipe whereas 29.8% were overweight/obese. Students who smoked waterpipe weekly had twofold greater odds of being obese than never-smokers (OR = 2.14; 95% CI = 1.08–4.21). Approximately 12% of students currently smoked waterpipe but not cigarettes, 2% smoked cigarettes but not waterpipe, and 11% smoked both. Body weight and age- and gender-specific BMI were greater for waterpipe and dual users compared to never users, especially for dual vs. never users (58.6 ±.8 vs. 55.6 ±.4 and.48 ±.07 vs..29 ±.03, respectively; p <.005). Conclusions : For dual users, greater frequency of tobacco use was associated with greater weight and BMI. Waterpipe and dual use is associated with greater obesity, BMI, and body weight among Jordanian adolescents. Given the rising epidemics of both tobacco use and obesity among Middle Eastern adolescents, the clustering of these risk factors warrants public health action.